\(L^{p}\)-approximation \((p ≥ 1)\) by Stancu-Kantorovich polynomials - Zoltán Finta (Journal of Numerical Analysis and Approximation Theory, 2002)
We establish direct and converse estimates for a generalized Kantorovich polynomial operator depending on a positive parameter.